Empirical evidence of students' systems thinking skills in ESD-oriented: A Rasch analysis approach - Ikmanisa Khairati; L. Lufri; Muhyiatul Fadilah (University of Muhammadiyah Malang, 2025)
Education for Sustainable Development (ESD) serves as a key accelerator for achieving the Sustainable Development Goals (SDGs), emphasizing systems thinking as an essential competency that must be cultivated in the learning process. This study investigates students' systems thinking skills within the ESD framework through assessments on environmental change—one of the core topics in biology education. Systems thinking enables students to analyze complex real-world phenomena by examining the interactions among system components and their role in forming an integrated whole. This descriptive quantitative study involved sixty 10th-grade students who were assessed using twelve essay questions, each designed to evaluate specific indicators of systems thinking within the ESD context. Data were analyzed using Rasch modeling in Winsteps, focusing on student ability levels, item validity, reliability, and Differential Item Functioning (DIF). Results indicated high item reliability, yet most students demonstrated pre-aware or emerging levels of systems thinking, particularly in identifying system components, recognizing interconnections, and applying systems thinking to sustainability issues. The low Person Measure Average suggests a pressing need for instructional improvements to strengthen students' systems thinking competencies. These findings underscore the necessity of integrating systems thinking into curricula to better prepare students for addressing sustainability challenges effectively.